Cotreatment with methotrexate in routine care patients with rheumatoid arthritis receiving biological treatment yields better outcomes over time. Issue 1 (22nd January 2019) - Boone, Niels W.; Sepriano, Alexandre; van der Kuy, Paul-Hugo; Janknegt, Rob; Peeters, Ralph; Landewé, Robert B. M.
Abstract : Objectives: We aimed to evaluate the effects of methotrexate (MTX) comedication added to biological disease-modifying antirheumatic drugs (bDMARD) on disease activity measures in patients with rheumatoid arthritis (RA) in routine care. Methods: Patients with RA on treatment with either bDMARDs or conventional synthetic DMARDs were included in this prospective cohort study. The effect of (time-varying) combination therapy with bDMARD and MTX compared with bDMARD monotherapy was tested in longitudinal generalised estimating equation models using as outcomes: (1) the likelihood to be in remission according to the 28-joint Disease Activity Score (DAS28) erythrocyte sedimentation rate (ESR) (<2.6) and to the Routine Assessment of Patient Index Data 3 (RAPID3) (0–30; ≤3), a patient-reported outcome measure about RA symptoms; and (2) DAS28-ESR and RAPID3 as continuous variables. All models were adjusted for potential confounders: age, gender, drugs for comorbidities (yes/no), oral steroids (yes/no) and non-steroidal anti-inflammatory drug (yes/no). Results: In total, 330 patients were included (mean (SD) follow-up; 10.7 (9.7) months). Compared with bDMARD monotherapy, MTX combination therapy was significantly associated with a 55% higher likelihood to be in DAS28 remission, but not RAPID3 remission, over time. Combination therapy resulted in slightly, but statistically significant, lower levels of DAS28-ESR over time (β=−0.42 (95% CI −0.67 to − 0.17)), but not RAPID3 (β=−0.58 (95% CI −0.65 to 0.49)). The effect on DAS28-ESR was entirely explained by lower swollen joint counts and was persistent after correction for confounders. Conclusion: These results give support to the policy that MTX should be continued in routine care patients with RA on biological therapy since this leads to better objective but not subjective clinical outcomes